Weaknesses in the Continuity of Care of Puerperal Women: An Integrative Literature Review - Ane Gabriele Poli Petersen; Adriane Cristina Bernat Kolankiewicz; Denise Casagrande; Pâmella Pluta; Vanessa Dalsasso Batista Winter; Fernanda Fernandes de Carvalho; Caroline Sissy Tronco (Revista Brasileira de Ginecologia e Obstetrícia, 2023)
Abstract The aim of the present study was to identify how the transition of care from the hospital to the community occurs from the perspective of puerperal women at risk. An integrative literature review was performed, with the question: “How does the transition of care for at-risk puerperal women from the hospital to the community occur?” The search period ranged from 2013 to 2020, in the following databases: PubMed, LILACS, SciELO, and Scopus. MESH, DeCS and Boolean operators “OR” and “AND” are used in the following crossover analysis:patient transfer ORtransition care ORcontinuity of patient care ORpatient discharge ANDpostpartum period, resulting in 6 articles. The findings denote discontinuity of care, given the frequency of non-adherence to the puerperal consultation. Transition studies of care in the puerperium were not found, which requires proposing new studies.